Incidence and Extent of Bruising After Subcutaneous Injection of Enoxaparin Sodium in Patients Hospitalized at Coronary Care Units - Zeynab Poursafar; Shirin Jafroudi; Mojgan Baghaei; Ehsan Kazemnezhad Leyli; Maryam Zarrizei (Guilan University of Medical Sciences, 2019)
Introduction: Bruising or ecchymosis after subcutaneous injection of enoxaparin sodium can cause anxiety and discomfort in the patient. Therefore, nurses should know the factors associated with the incidence and extent of this complication. Objective: This study aims to investigate incidence and extent of bruising after subcutaneous injection of enoxaparin sodium and its related factors in patients hospitalized at coronary care unit of Dr. Heshmat educational and treatment center in Rasht City, Iran. Materials and Methods: This analytical cross-sectional study was conducted on 84 patients hospitalized at coronary care unit in 2015. They were under treatment with enoxaparin sodium 6000 IU. The samples were selected using consecutive sampling method. To standardize the injection method, all injections were performed by one nurse as the member of research team at the right side of the abdomen and above the navel in 10 seconds (using a chronometer). Evaluation of the incidence and extent of bruising was done by a trained nurse 48 hours after the injection. The study instrument consists of demographic-clinical characteristics of the patients and records of the incidence and extent of bruising. These data were collected by interview, observation, and measurement using a flexible transparent ruler. The incidence and extent of bruising (under three categories of "insignificant bruise", "small bruise", and "large bruise") were analyzed using descriptive (frequency, mean, standard deviation) and inferential (Chi-squared test, Independent t-test, and ANOVA) statistics. Results: The majority of the study samples were women (65.5%) with a mean age of 66±11 years. Bruising was seen in 53.6% of samples of which 56% of them had insignificant bruising, 23% small bruises, and 21% large bruises. The incidence of bruising had significant relationship with hyperlipidemia (P=0.028) and the extent of bruising was significantly correlated with hypertension (P=0.048). Conclusion: Based on the results, we should consider and screen hyperlipidemia and hypertension in the patients with heart problems treated with enoxaparin sodium with respect to the incidence and extent of bruising.